Britain and the war on terror policy, strategy and operations - Chin, Warren (Military strategy and operational art, 2013)
Why did Britain come to play such a prominent role in the war on terror and why did the military instrument come to be the dominant theme in the British prosecution of what was an ideological and political struggle? This book is an analysis of Britain's war against Al Qaeda and the phenomenon of international terrorism which marked a paradigm shift in the nature and conduct of war in the twenty-first century. At the heart of the book is an attempt to understand why Britain, which possessed a wealth of experience in the conduct of counterterrorism, counterinsurgency and small wars, developed a strategic and operational design to defeat the Islamist threat which proved to be deeply flawed. In addressing this question the book explores the complex intellectual, doctrinal and geopolitical challenge posed by Al Qaeda and international terrorism and how and why the British response took the form that it did. In conducting this analysis the book raises important questions about the assumptions and perceptions of those in government who led the UK into this conflict, the nature of the civil military relationship in Britain and how well it functioned, and finally the competence of its security forces in being able to deal with this threat both domestically and overseas.